What is better for psychiatry: Titrated or fixed concentrations of nitrous oxide? - Gillman, Mark A. (Frontiers in Psychiatry, 2022)
Medication dosages are crucial –no single dose fits all. My paper compares the safety, scientific and practical applicability of fixed 25-50% concentrations of nitrous oxide (N2O) with the variable titrated concentrations of Psychotropic Analgesic N2O (PAN), as used in dentistry, and neuropsychiatry. A crucial difference is that PAN is always titrated, via an open circuit (nasal mask), to the minimum concentration (dose), which ensures full consciousness, cooperation, comfort and relaxation. With PAN, the goal is subject comfort, not dose. In contrast, fixed goal concentrations are usually given via relatively closed circuits (full facial mask/similar) without account for individual patient’s dose-response. Hence, fixed concentrations, in N2O sensitive subjects, could result in unconsciousness and other adverse effects (nausea, vomiting, anxiety, aspiration, might occur; requiring an anaesthesiologist for patient safety. PAN is titrated using each subject’s subjective and objective responses as the guide to the ideal concentration. Thus, when PAN is used, there is no fixed concentration even for a single subject, nor is an anaesthesiologist required. Furthermore, there is a greater scientific rationale for using PAN, because the receptor systems involved are better known, whilst those for fixed concentrations are not. The PAN or dental titration method has been safely used in general dentistry for over 70 years and as an investigative, diagnostic and therapeutic tool for neuropsychiatry for over 40 years. Clinical applications include substance abuse detoxification, ameliorating depression, and investigations of schizophrenia, human orgasm, pain perception and basic neuroscience. By contrast, the experience with fixed doses in psychiatry is limited.